Peningkatan Kemampuan Menyimak Cerita Fantasi Melalui Media Audiovisual Siswa Kelas VII SMP Negeri 4 Gunungsitoli Selatan - Ndraha, Laurensia; Lase, Julita Hertawati; Harefa, Esther Novi Christin; Zega, Elsa Fitriana; Waruwu, Lestari (Indo-MathEdu Intellectuals Journal, 2023)
Listening is something that requires genuine care and attention. This study aims to determine audiovisual-based learning on fantasy story material in students of SMP Negeri 4 South Gunungsitoli. This study is Classroom Action Research (PTK). 26 grade VII students were used as data sources for this study. The method of data analysis is carried out qualitatively. The research was conducted in two cycles, cycle I and cycle II, each of which lasted for four times the learning process. The findings of this study showed that twenty-two students were able to understand the material quite well. Therefore, it can be concluded that audiovisual learning media can help students listen to story material